1979
DOI: 10.1148/132.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Hemangioma of the Liver: Ultrasonography, Arteriography, and Computed Tomography

Abstract: Gray-scale ultrasonography and angiography were performed on 5 patients with cavernous hemangioma of the liver. Four patients also had radionuclide scans and 2 had computed tomography. Angiography was the most specific diagnostic examination; the findings of the other 3 techniques were nonspecific, yet valuable for initial identification of the lesions and their characterization as solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(16 citation statements)
references
References 5 publications
1
9
0
4
Order By: Relevance
“…It has been suggested that if a lesion is ultrasonically demonstrated to be cystic, diagnosis of a benign cystic lesion can generally be made and no further procedures need to be performed. 36 However, we as well as others3' have seen cavitary metastatic tumors in the liver simulating hepatic cysts on ultrasound studies. Aspiration of an echinococcus cyst should be contraindicated for fear of potential anaphylactic shock.…”
Section: Discussionsupporting
confidence: 48%
“…It has been suggested that if a lesion is ultrasonically demonstrated to be cystic, diagnosis of a benign cystic lesion can generally be made and no further procedures need to be performed. 36 However, we as well as others3' have seen cavitary metastatic tumors in the liver simulating hepatic cysts on ultrasound studies. Aspiration of an echinococcus cyst should be contraindicated for fear of potential anaphylactic shock.…”
Section: Discussionsupporting
confidence: 48%
“…The results of many studies (1)(2)(3)(4)(5)(6)(7)(8) have documented the ultrasonographic (US) appearance of hepatic hemangiomas. The typical appearance is that of a hyperechoic, well-defined lesion with or without small central regions of decreased echogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Their differentiation from malignant liver tumors is important because hepatic hemangiomas usually require no treatment. 2 The utility of enhanced computed tomography (CT) and gadolinium-diethylenetriaminepentaacetic acid (Gd-DTPA)-enhanced magnetic resonance (MR) imaging has been reported for the diagnosis of hepatic hemangiomas and their differentiation from malignant liver tumors. [3][4][5][6][7][8][9] The most common features of hepatic hemangiomas on enhanced CT and Gd-DTPA-enhanced MR imaging are peripheral or central nodular enhancement during the arterial phase, fill-in enhancement during the portal venous phase, and prolonged enhancement during the late phase.…”
Section: Introductionmentioning
confidence: 99%